Eco-friendly Removal of Methylene Blue Using Alginate-Activated Natural Clay Composite - Rasidah, Rasidah; Jumiati, Jumiati; Nugroho, Wahyu; Agnestisia, Retno; Karelius, Karelius; Alfanaar, Rokiy; Muhamad Iqbal, Rendy (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2023)
Methylene blue is a poisonous, persistent, and non-biodegradable dye frequently found in textile industry wastewater that significantly influences the emergence of various environmental and health problems. Therefore, precautions must be taken to reduce the amount of methylene blue in the wastewater. Compositing clay into alginate produces an eco-friendly adsorbent, alginate-activated clay composite beads (Ag-AC 1-5%), successfully removing methylene blue. XRD and FTIR spectroscopy characterization results show that illite, a family of 2:1 clay minerals, is a primary constituent of activated clay. However, FTIR spectroscopy shows that alginate has mannuronic acid residue characteristics. Several batch experiments were carried out to evaluate the effect of the alginate: clay ratio and pH solution on the percentage of methylene blue removal.